Effect of source and levels of sulphur on yield and nutrient uptake by pearl millet - Singh, Harvendra; Bhadoria, Harendra Singh (Annals of Agricultural Research, 2014)
Field experiments were conducted at Gwalior (M.P.) during rainy season of 2008 and 2009 to evaluate the effect of sources and levels of sulphur on productivity of pearl millet. The results revealed that each successive increase in the level of sulphur up to 40 kg S /ha significantly increased the grain and stover yield and total uptake of N, P and S in crop. However, protein yield, available N, P and S in soil after harvest of the crop were recorded to be increased up to 60 kg / ha. Amongst the various source of sulphur tested, ammonium sulphate was the best in respect of grain and stover yield, protein content as well as uptake of nutrients by the crop and also available N status in soil.